Efektivitas Pelaksanaan Kewenangan Kepala Desa dalam Pembinaan Masyarakat di Desa Karangrejo Kesesi Pekalongan - sulam janah; Karimatul Khasanah (Manabia: Journal of Constitutional Law, 2022)
The main tasks of the village head based on article 26 paragraph 1 of Law Number 6 of 2014 concerning villages include implementing community development, in terms of whether community development has been carried out by the Karangrejo village head, Kesesi District, direct research in the village is needed. Therefore, the purpose of this study is to find out how effective the effectiveness of the implementation of the village head's authority in community development is as stated in Law Number 16 of 2014 concerning villages, as well as the implications in the case that the Karangrejo Village Head, Kesesi District does not exercise his authority. In Karangrejo village, Kesesi District, the law enforcement factor where this is carried out by the village head in his authority to carry out community development, has not been fully implemented. The implication is that if the village head does not carry out his duties, he can be dismissed, then interact with the community and of course will hinder the process of implementing development and empowering village communities, because it can be said to be successful. according to the rules, and can do business in the community.